Retained Surgical Gauze Presenting With Gross Hematuria: A Case Report - Javanmard, Babak; Yousefi, Mohammad Reza; Fadavi, Behrouz; Fallah Karkan, Morteza (Urology Journal, 2017)
Gossipyboma is a mass which is made around a cotton sponge or abdominal compress retained in a patient during surgery accidentally. Patients manifest with either acute or chronic symptoms due to complications. Here in we reported an 89-year-old man case of transvesical migration of gossipyboma who presented with gross hematuria with a history of transvesical prostatectomy 6 years ago. Patient underwent exploratory laparotomy with repairing of the bladder and peritoneum. He had no complications during surgery and was subsequently discharged.